The Impact of Social Media on Entrepreneurship in Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Social media has emerged as a critical driver of entrepreneurial activity in contemporary economies, particularly in developing countries such as Nigeria where traditional business infrastructures are often limited. Digital platforms including Facebook, Instagram, WhatsApp, X (formerly Twitter), TikTok, and LinkedIn have transformed how entrepreneurs identify opportunities, promote products and services, interact with customers, and scale their ventures. By lowering entry barriers and reducing marketing and transaction costs, social media enables Nigerian entrepreneurs—especially small and medium-sized enterprise (SME) owners and informal sector operators—to compete beyond local markets and reach diverse consumer segments.This article examines the impact of social media on entrepreneurship in Nigeria, with particular attention to its role in innovation, brand visibility, market access, customer relationship management, and overall entrepreneurial performance. Drawing on existing academic literature, policy reports, and contextual examples from Nigerian SMEs, the study highlights how social media supports product innovation through customer feedback, strengthens brand development through visual and interactive content, and facilitates market expansion through targeted advertising and online networks. The findings suggest that entrepreneurs who strategically integrate social media into their business models and possess adequate digital and entrepreneurial skills tend to experience improved sales performance, customer loyalty, and business sustainability.Despite these benefits, the article also identifies key challenges associated with social media–driven entrepreneurship in Nigeria. These include intense market competition and saturation, reputational and cyber risks, misinformation, unreliable digital infrastructure, and overdependence on platform algorithms that can unpredictably affect business visibility. The study argues that without appropriate skills, regulatory awareness, and supportive digital policies, these challenges may undermine the long-term benefits of social media adoption.Overall, the article contributes to IT and entrepreneurship scholarship by offering a balanced, context-specific analysis of social media’s role in Nigerian entrepreneurship, providing insights relevant for academics, policymakers, and practitioners seeking to leverage digital platforms for inclusive and sustainable economic development.